Break-up of the largest Arctic ice shelf and associated loss of an epishelf lake - Mueller, D. (Derek); Vincent, W.F. (Warwick F.); Jeffries, M.O. (Martin O.) (Geophysical Research Letters, 2003)
Field observations and RADARSAT imagery of the Ward Hunt Ice Shelf (lat. 83°N, long. 74°W), Nunavut, Canada, show that it broke in two over the period 2000 to 2002, with additional fissuring and further ice island calving. The fracturing caused the drainage of an ice-dammed epishelf lake (Disraeli Fiord), a rare ecosystem type. Reductions in the freshwater volume of Disraeli Fiord occurred from 1967 to the present and accompanied a significant rise in mean annual air temperature over the same period in this far northern region. The recent collapse of ice shelves in West Antarctica has been interpreted as evidence of accelerated climate change in that region. Similarly, the inferred thinning and observed fragmentation of the ice shelf, plus the drainage of the epishelf lake, are additional evidence for climate change in the High Arctic.